Hound dog - Pégon, Nicolas 1984- (Éditions Denoël, 2022)
When César and Alexandre find a lost dog and begin a search for its owner. Their search across a post-apocalyptic United States only leads to new mysteries as they are guided by the spit of Elvis Presley
Keywords: Lost dogs / Comic books, strips, etc; Presley, Elvis / 1935-1977 / Comic books, strips, etc; Detective and mystery comics; Graphic novels; Comics (Graphic works); Comic